Determination of lead in milk samples using vortex assisted deep eutectic solvent based liquid phase microextraction-slotted quartz tube-flame atomic absorption spectrometry system - Borahan, Tulay; Unutkan, Tugce; Turan, Nouha Bakaraki; Turak, Fatma; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2019)
Determination of lead at trace levels was achieved by slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS) after the preconcentration with deep eutectic solvent-based liquid phase microextraction (DES-LPME). A green solvent was used to extract lead from the aqueous solution. Parameters affecting the extraction efficiency and determination were optimized in the aim to lower the detection limit. Under the optimum experimental and instrumental conditions, the proposed method exhibited a linear range between 50 and 1000 mu g L-1, and the limits of detection and quantitation (LOD and LOQ) were found to be 8.7 and 29.0 mu g L-1, respectively. The detection power was improved by 48 times using DES-LPME-SQT-FAAS method with respect to conventional FAAS system. Recovery studies were carried out in raw milk samples to check the accuracy and the applicability of the developed method and the percent recoveries obtained were between 102.5 and 103.2% for the spiked raw milk samples.
Keywords: Deep eutectic solvent; Lead; Liquid phase microextraction; Flame atomic absorption spectrometry; WATER SAMPLES; HEAVY-METALS; CADMIUM; NICKEL; ELEMENTS; DISEASE; BURDEN; COBALT; COPPER; FLOW; Chemistry; Food Science & Technology; Nutrition & Dietetics